Avoiding poor health or approaching good health: Does it matter? The conceptualization, measurement, and consequences of health regulatory focus1. Issue 4 (26th February 2013) - Gomez, Pierrick; Borges, Adilson; Pechmann, Cornelia (Connie)
Abstract: This research presents a new scale, the health regulatory focus scale, which measures an individual's tendency to use promotion or prevention strategies in the pursuit of health goals. We conducted five studies in France to develop the scale which is made up of two subscales for prevention and promotion. We also tested the scale's psychometric properties and demonstrated its two‐factor dimensionality, internal and test–retest reliability, and convergent, nomological, predictive and discriminant validity. The health subscales showed good predictive validity in that they correlated with health behaviors better than the general regulatory focus subscales. For instance, health promotion focus predicted dentist visits while general promotion focus did not, and health prevention focus predicted the use of prescription and over‐the‐counter drugs while general prevention focus did not. Also as expected, general prevention focus predicted avoidance of risky vacation behaviors while health prevention focus did not. The health subscales either did not correlate or correlated weakly with positive and negative affectivity and general risk aversion indicating good discriminant validity. The one‐year test–retest reliabilities were adequate for both subscales.